PERSPEKTIF SIKLUS HIDUP PERUSAHAAN DALAM HUBUNGAN ANTARA INVENTORI DAN KINERJA FINANSIAL - Ferry Setiawan; Nofrisel Nofrisel (Jurnal Ekonomi dan Bisnis, 2019)
Research regarding the relationship between inventory management and financial performanceis so far inconclusive: some found it to be positive, others found it to be negative. One ofthe many factors that influence the variance, the organizational life cycle, will be exploredin this research. Organizational life cycle might influence the relationship between inventorymanagement and financial perfomance due to the different strategies and designs pursuedby the organizations along each of their life cycle stages. This study use a sample set of 33manufacturing companies listed in BEI, with 7 years observation period. A regression analysisis performed with dummy variables of organizational life cycle, resulting from a cluster analysiswith k-mean method. Regression analysis and cluster analysis are all done with Stata. Theresult shows that the relationship between inventory and financial performance is positive inthe early growth stage of organization life cycle and turns to negative at late growth stage. Therelationship is inconclusive at the conception and stability stage of organizational life cycle.Therefore, we can conclude that in making decisions about inventory, firms should considerwhat stage of organizational life cycle they are currently in so that the decisions made canimpact the financial performance positively.Keywords: Organizational Life Cycle, Financial Performance, Inventory Management